A study on the defluoridation in water by using natural soil - Chidambaram, S.; Manikandan, S.; Ramanathan, A.; Prasanna, Mohan Viswanathan; Thivya, C.; Karmegam, U.; Thilagavathi, R.; Rajkumar, K. (SpringerOpen, 2013)
Removal of excess fluoride (F−) from the water has been attempted by several authors by using different materials both natural and artificial. The main aim of this paper was to attempt the fluoride removal by using the locally available red soil adopting column method. The red soil was mixed in different proportion with sand in order to increase the porosity and permeability property of the medium. It was optimized for 4:1 ratio of red soil to sand and it was used for the following experiment. The experiment was conducted in 11 batches for a period of about 9,213 min. Fresh standard solution of F was used in each batch, prepared from Orion 1,000 ppm solution. The samples were collected and analyzed for pH, EC (Electrical Conductivity) and HCO3. Rate of flow of water and efficiency of adsorption were calculated and compared with the fluoride removal capacities of the medium. The medium used for the fluoride removal was subjected to FTIR analysis before and after the experiment. The variation of IR spectrum before and after treatment signifies the changes in the OH bonding between Al and Fe ions present in the soil. The variation in pH decreased during the course of defluoridation. Higher F removal was noted when flow rate was lesser. An attempt on the regeneration of the fluoride adsorbed soil was also made and found to be effective.